New insights of processionary moth, Thaumetopoea cheela on pistachio nut (Pistacia vera): Interaction effect on flowering and nut yield - CHANDEL, RAJESHWAR S; SINGH, JOGINDER; SHARMA, P L; KUMAR, RAKESH; KUMAR, PRAMOD (The Indian Journal of Agricultural Sciences, 2019)
The processionary moth, Thaumetopoea cheela (Moore) was found as a serious defoliator of Pistachio nut (Pistacia vera L.), which is a new record. The development of egg, larva and pupa was completed in 196.5±0.40, 68.1±1.97 and 86.9±0.62 days, respectively. The adult longevity was 2–3 days and each female laid an average of 179 eggs in a cluster. The insect overwintered in egg stage. The moth followed Dyar’s law and the Dyar’s ratio varied from 1.67–1.73. The occurrence and severity of this pest on the sparse host plantation warrants its regular monitoring on other possible alternate hosts and development of IPM strategy.The magnitude of the damage depends on the extent of defoliation, time of incidence and the vigour of the affected tree. Leaf defoliation prior to development of flower buds reduced the number of reproductive stalks, flower buds, flowers and the nut yield of pistachio plantation.